Immunoadsorption study Mainz in adults with post-COVID syndrome (IAMPOCO)—a single-blinded sham-controlled crossover trial to evaluate the effect of immunoadsorption on post-COVID syndrome - Marco Stortz; Pascal Klimpke; Andreas Kommer; Philipp Gründer; Livia Steenken; Christian Dresel; Daniel Kraus; Irene Schmidtmann; Arndt Weinmann; Julia Weinmann-Menke (Trials)
Abstract Background Post-COVID syndrome (PCS) affects up to 43% of all SARS-CoV-2-infected persons and describes ongoing symptoms months after the acute infection. Despite the large number of affected people, there is still very little evidence about therapeutic options. Some studies suggest at least partially a role of autoantibody-mediated autoimmunity. Immunoadsorption is an extracorporeal therapy to remove circulating antibodies which is used successfully in several autoimmune diseases. We conceived the IAMPOCO trial to evaluate the therapeutic effect of immunoadsorption in patients with PCS. Methods IAMPOCO is a single-center randomized sham-controlled trial with a crossover design which will enroll 40 participants with PCS and a symptom severity of at least 2 on post-COVID functional scale. All participants will undergo 5 immunoadsorption treatments and after a washout period of 8 weeks 5 sham treatments or vice versa. Which modality is conducted first will be randomized. Patients but not providers of therapy are blinded for which modality is conducted. Primary outcome is the efficacy of IA to the severity of PCS measured by the change of several symptom scores and hand grip strength. Secondary outcomes are the frequency of adverse events and the prevalence of relevant autoantibodies in participants with PCS as well as the concentration of autoantibodies before and after therapy and sham treatment. Discussion The trial addresses the lack of evidence for treatment options in PCS. By using a crossover design and including a sham treatment arm, the study aims to compare the effects of immunoadsorption and sham therapy within the same patients. The trial also benefits from recruiting participants from a cohort study on PCS prevalence, ensuring a thorough evaluation of symptoms. Objective assessments of symptoms are challenging due to their subjective nature, but various scoring systems and tests are being utilized. Despite the lack of data from RCTs, the results of this study have the potential to significantly improve PCS therapy and support evidence-based treatment decisions. Trial registration ClinicalTrials.gov NCT05841498. Registered on May 3, 2023.